Analisis Pengaruh Modal Kerja, Luas Lahan, dan Fluktuasi Harga Jual terhadap Profitabilitas Usaha Tani di Desa Banjar, Kecamatan Taliwang, Kabupaten Sumbawa Barat - Jihan Ashari; Arya Zulfikar Akbar (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the effects of working capital, land area, and selling-price fluctuation management on farm profitability in Banjar Village, Taliwang District, West Sumbawa Regency. The study applies a quantitative explanatory cross-sectional design and Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. The target population consists of farmers who reside in or operate farms in Banjar Village, while 100 respondents are selected through purposive sampling and the Paul Leedy formula for an unidentified population. Four reflective constructs are measured through 16 statements on a four-point Likert scale. The measurement model satisfies convergent validity, discriminant validity, and internal consistency criteria. Bootstrapping with 5,000 subsamples shows that working capital (β = 0.410; t = 6.094; p < 0.001), land area (β = 0.314; t = 4.341; p < 0.001), and selling-price fluctuation management (β = 0.414; t = 6.845; p < 0.001) positively affect farm profitability. The structural model explains 60.1% of profitability variance and demonstrates predictive relevance. The findings emphasize the complementary roles of seasonal liquidity, economically viable land scale, timely market information, flexible selling decisions, and margin-protection practices in strengthening smallholder profitability.